Long Noncoding RNA RP11-115N4.1 Promotes Inflammatory Responses by Interacting With HNRNPH3 and Enhancing the Transcription of HSP70 in Unexplained Recurrent Spontaneous Abortion - Liu, Meilan; Sun, Xiaoyue; Zhu, Liqiong; Zhu, Menglan; Deng, Kewen; Nie, Xiaolu; Mo, Hanjie; Du, Tao; Huang, Bingqian; Hu, Lihao; Liang, Liuhong; Wang, Dongyan; et al. (Frontiers in Immunology, 2021)
Background: Unexplained recurrent spontaneous abortion (URSA) is a common pathological problem in pregnancy and the etiology is complicated. URSA-associated lncRNAs are expected to be potential biomarkers for diagnosis, and might be related to the disease pathogenesis. Objective: To investigate differential lncRNAs in peripheral blood of non-pregnant URSA and normal control women and to explore the possible mechanism of differential lncRNAs leading to URSA. Methods: We profiled lncRNAs expression in peripheral blood from 5 non-pregnant URSA patients and 5 matched controls by lncRNA microarray analysis. Functions of URSA-associated lncRNAs were further investigated in vitro. Results: RP11-115N4.1 was identified as the most differentially expressed lncRNA which was highly upregulated in peripheral blood of non-pregnant URSA patients (P = 3.63E-07, Fold change = 2.96), and this dysregulation was further validated in approximately 26.67% additional patients (4/15). RP11-115N4.1 expression was detected in both lymphocytes and monocytes of human peripheral blood, and in vitro overexpression of RP11-115N4.1 decreased cell proliferation in K562 cells significantly. Furthermore, heat-shock HSP70 genes (HSPA1A and HSPA1B) were found to be significantly upregulated upon RP11-115N4.1 overexpression by transcriptome analysis (HSPA1A (P = 4.39E-08, Fold change = 4.17), HSPA1B (P = 2.26E-06, Fold change = 2.99)). RNA pull down and RNA immunoprecipitation assay (RIP) analysis demonstrated that RP11-115N4.1 bound to HNRNPH3 protein directly, which in turn activate heat-shock proteins (HSP70) analyzed by protein-protein interaction and HNRNPH3 knockdown assays. Most importantly, the high expression of HSP70 was also verified in the serum of URSA patients and the supernatant of K562 cells with RP11-115N4.1 activation, and HSP70 in supernatant can exacerbate inflammatory responses in monocytes by inducing IL-6, IL-1β and TNF-α and inhibit the migration of trophoblast cells, which might associate with URSA. Conclusion: Our results demonstrated that the activation of RP11-115N4.1 can significantly increase the protein level of HSP70 via binding to HNRNPH3, which may modulate the immune responses and related to URSA. Moreover, RP11-115N4.1 was expected to be a novel etiological biomarker and a new therapeutic target for URSA.